Contraction force specificity and its relationship to functional performance - Harris, N.; Cronin, J.; Keogh, J. (Journal of Sports Sciences, 2007)
Best practice for improving strength and power through resistance strength training has been the subject of much research and subsequent conjecture. Much of the conjecture can be attributed to methodological discrepancies. The type of dynamometry used in testing, the training experience of research participants, the specific technique employed in a lift, and the methods of collection and calculation all impact on the final variables of interest. This review examines contraction force specificity by first addressing the methodological issues surrounding our interpretation of the results. Then we address the kinematics and kinetics associated with single and multiple repetitions in relation to the development of strength, power, and functional performance. This discussion provides the delimitations for analysis of subsequent training studies. Finally, recommendations are formulated with the aim of assisting assessment and training practice as well as providing directions for future research. The results of this review suggest that the enhancements in performance resulting from resistance training are context specific in experienced resistance-trained participants. Thus, specific conditioning could be required to achieve improvements in functional performance in this group.